Síntese e caracterização de 1,3,4-oxadiazolil-1,2,4-oxadiazóis derivados de ácidos acrílicos 3-substituídos - Mayer, João Cândido Pilar (2017)
A series of 1,3,4-oxadiazolyl-1,2,4-oxadiazoles was synthesized through a one-pot condensation-cyclization reaction between 3-substituted acrylic acids and 5-aryl-1,2,4-oxadiazolyl-1,2,4-oxadiazoles, and were characterized through 1H NMR, 13C NMR, X-ray diffraction and HRMS. Products were obtained in rather variable yields (23 – 87 %). The cited compounds were compared to single heterocycle-containing (1,3,4-oxadiazole) examples in order to measure the influence of the 1,2,4-oxadiazole, as well as the substituents’, on the molecules. After a simple comparison of 1H NMR signs between cinnamic acid derivatives, two series of (E)-3-ferrocenylacrylic acid derivatives were characterized through UV-Vis spectroscopy and cyclic voltammetry. They were also tested for ct-DNA interaction, displaying strong interaction (K~106 M-1) with it. Finally, crotonic acid derivatives were reactive to the aminoacid cysteine, giving a series of adducts, which suggests a possible activity in future biological tests.